Market reaction to transparency: An empirical study on life insurance demand in Europe - Ming Dong (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2014)
This article explores life insurance consumption in 31 European countries from 2003 to 2012 and aims to investigate the extent to which market transparency can affect life insurance demand. The cross-country evidence for the entire sample period shows that greater market transparency, which resolves asymmetric information, can generate a higher demand for life insurance. However, when considering the financial crisis period (2008-2012) separately, the results suggest a negative impact of enhanced market transparency on life insurance consumption. The mixed findings imply a trade-off between the reduction in adverse selection under greater market transparency and the possible negative effects on life insurance consumption during the crisis period due to more effective market discipline. Furthermore, this article studies the extent to which transparency can influence the reaction of life insurance demand to bad market outcomes: i.e., low solvency ratios or low profitability. The results indicate that the markets with bad outcomes generate higher life insurance demand under greater transparency compared to the markets that also experience bad outcomes but are less transparent.
Keywords: G14; G22; 330; life insurance demand; transparency; market discipline